"FlexPad" - Innovative conical sliding bearing for the main shaft of wind turbines. (May 2019) - Schröder, Tim; Jacobs, Georg; Rolink, Amadeus; Bosse, Dennis
Abstract: This paper shows an innovative approach concerning a new type of rotor main bearings for wind turbines. The conical sliding bearing with its flexible support structure is designed for the specific loads and operating conditions of wind turbines. It is robust, compact and offers superior serviceability since individually replaceable bearing pads obviate the disassembling of the whole drivetrain during repair/maintenance. After a short description of the bearing design the results of functional testing under real conditions in full-scale on a 1 MW system test bench are presented. The achieved load-bearing properties, the mixed friction performance and the start-up behaviour will be discussed.